THE EVALUATION OF THE NEW STUDENT ONLINE ADMISSIONS POLICY (PPDB) IN GORONTALO PROVINCE - RITA HULANTU; Bala Bakri; Sri Yulianty Mozin (Jurnal Ilmu Manajemen dan Bisnis, 2021)
The objectives of this research are: 1) to analyze the implementation process of PPDB Online system and find the obstacles faced in the implementation of the online PPDB system in SMK Negeri 2 Gorontalo school year 2020/2021; 2) to evaluate the policy that has been implemented by SMK Negeri 2 Gorontalo the process of implementing PPDB online and whether the policy that has been implemented can run well and provide solutions to the implementation process of ppdb online; 3) to evaluate the factors that inhibit the policy that has been run by smk Negeri 2 Gorontalo online PPDB implementation process. This research uses qualitative approach. To obtain objective results, qualitative research is conducted by exploring and breaking through the symptoms that interpret the problem or conclude the combination of various problems as presented by the situation. The results showed that: 1) in the Process of Implementing PPDB Online At SMK Negeri 2 Gorontalo School Year 2020/2021 judging from the flow of acceptance of new students has been run well, but the results have not been efficient; 2) implementation of PPDB Online Policy in SMK Negeri 2 Gorontalo judging by the number of acceptable learners, registration system, selection system, and registration time is still not running effectively so that the results are not efficient; 3) The factors that hinder the implementation of ppdb policy online are constraints on the use of applications, and constraints on internet connection.